Analisa Perbandingan Pengaruh Bauran Pemasaran Produk Pelumas Merek Global dan Merek Global Terhadap Kepuasan Pembelian - Marceilla Marceilla (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research aims to determine whether there is a effect with marketing mix to purchase satisfaction and whether it relates to marketing global product mix and local brands to purchase satisfaction by conducting a survey of 143 respondents using global and/or local lubricants brand.. The independent variable used in this study is the marketing mix, namely product, price, place and promotion, while the dependent variable in this study is purchase satisfaction. This type of research is explanatory research with quantitative research. The location of the study was conducted at Jasmine Mansion Mansion Kemayoran, Jakarta. Data analysis techniques used descriptive analysis, regression analysis and comparative analysis using SPSS for Windows 25. The results of this study indicate product variables, prices, places and promotions related to purchases, both simultaneously and partially. From the results of comparative analysis shows there is no difference between product variables, price, place and promotion of global and local brand lubricant products to purchase satisfaction